SPIRITUAL COMPANY AS A PREDICTOR OF COMPANY SUSTAINABILITY AND PERFORMANCE - SOEPRAPTO, ADI; SUGIARTO, MEILAN; SUSI DEWANTI, IDA; ASTUTI DEWI, MACHYA (Qawwam : The Leader's Writing, 2025)
The background of this research is driven by increasingly intense demands from stakeholders for companies to not only focus on financial profits, but also to be responsible for social and environmental sustainability. The concept of Spiritual Company, which encompasses values such as integrity, meaning in work, caring for others, and a balance between profit and ethical responsibility, is seen as a crucial predictor of corporate sustainability and overall performance. This study aims to explore the influence of the Spiritual Company concept on corporate sustainability and performance through a qualitative approach and identify the mechanisms, supporting factors, and obstacles that arise in the relationship between Spiritual Company and these two variables. The method used is qualitative research with case studies or in-depth interviews involving company leaders, managers, and employees as informants. Data is processed through thematic analysis, open coding, and data source triangulation to ensure the validity and reliability of the research findings. The results of the study revealed that companies that apply spiritual values in their organizational culture, including ethical leadership, employee empowerment, internal justice, and attention to social and environmental aspects, tend to perform better in maintaining sustainability in the economic, social, and environmental dimensions. In addition, Spiritual Companies also contribute positively to company performance, including productivity, job satisfaction, reputation, and competitiveness. However, obstacles are encountered, such as a lack of commitment from leaders, conflicts with short-term profit goals, and ambiguity in implementing spiritual values at the operational level. In conclusion, Spiritual Companies have proven to be significant corporate sustainability and performance predictors. To optimize the benefits, companies should consistently internalize spiritual values and incorporate them into their strategies, policies, and daily operational practices.